Role of Thermal Treatment in Stress Failure of Concrete Differing in its Aggregate Grain Composition - Hoła, J. (Engineering Transactions, 1996)
Results of tests aimed at determining the influence of heat treatment on the stress failure of concrete differing significantly in its aggregate grading are presented. Seven batches of concrete, having similar compressive strengths but differing radically in their grain composition, were tested. The specimens were subjected to heat treatment in low-pressure steam in an identical temperature-time cycle. It has been shown that the course of destruction of the specimens made from different mixes is determined by heat treatment, no matter what is the fine aggregate content in the concrete. This is demonstrated above all by the values of initiating stress σ; and critical stress σcr, determined in the tested mixes and compared with the values of these stresses in the analogous but normally cured concrete mixes.